The Silence of Intellectuals: Philosophy, Politics and Parrhesia in Foucault - Alzola Molina, Aitor (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
During the 1980s, a controversy known as «the silence of intellectuals» broke out in France. In this article, we will address the unique position of Michel Foucault. In order to do this, we will move in two directions. Firstly, we will argue the following hypothesis: the foundation of his ideas in this polemic can be found in his analysis of parrhesia from the 1980s onwards. Secondly, we will look at authors such as Lyotard and Blanchot, who took part in the argument with well-known analysis, in order to point out the particularity of Foucault’s reflection. In this way, we attempt, not only to highlight his original contribution to the problem, but also to indicate the differences between this approach and his previous critique of the intellectual from the 1970s.